JENIS-JENIS TANAMAN DAN PENGELOLAAN DI HOTEL BERBINTANG KAWASAN PARIWISATA UBUD - Afrianingsih, Sri; Ginantra, I Ketut; Muksin, I Ketut (SIMBIOSIS, 2019)
This research is aimed to determine plants species in 3 hotels, by grouping them into rare plants, medicinal plants, water-saving plants and how to manage them. The sample was obtained by a simple random sampling technique on the entire starred hotels in Ubud. The hotels which are the object of research are the Four Seasons, Maya Ubud, and The Royal Pita Maha. Data collection is done by doing observation, literature study, document checking and interviews. The type of data used is quantitative and qualitative data with the types of data sources are primary and secondary. Data analysis which used in this study are descriptive qualitative and quantitative. The results of this research in  Four Seasons hotel are found 38 plants species from 24 families which 17 species grouped into rare / protected plants, 14  medicinal plants species and 15 water-saving plants species. Next, in the Maya Ubud hotel found 48 plants species from 27 families which grouped into 26 species of rare / protected plants, 15 medicinal plants species and 18 water-saving plants. The last, at The Royal Pita Maha hotel found 45 plants species from 24 families which grouped into 27 rare / protected plants species , 8 medicinal plants species and 21 water-saving plants. Plants management method of those hotels is loose ground, selecting superior seeds, cleaning weeds, using organic fertilizers, pest controlling, and arranging watering schedules.